2019
DOI: 10.26842/binhm.7.2019.15.4.0381
|View full text |Cite
|
Sign up to set email alerts
|

The Diurnal Birds of Prey (Raptors) in the Mesopotamian Marshes of Southern Iraq With Notes on Their Conservation Status

Abstract: Birds of prey (Raptors) are top predator avian species that many migrate annually through Mesopotamian marshes in southern Iraq toward their wintering grounds in Arabia and Africa, while others are breeding residents; however, information on their current status is scarce. From January 2016 to April 2019, a total of 20 field expeditions were conducted in the geographical zone of the Mesopotamian marshes, wetlands of international importance. The survey covered the Central Marshes, Al-Hammar and Hawizeh Marsh. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…During our field surveys, we encountered multiple other species of raptors inside the study area. We included their IUCN conservation status and their taxonomic order following Al-Sheikhly and Al-Azawi (2019b) DISCUSSION The Western marsh harrier has been a regular raptor in the Mesopotamian wetlands, having been recorded on a regular basis starting in the 1920s (Al-Sheikhly and Al-Azawi, 2019a). However, few research efforts have been conducted with regard to its migrating/wintering population.…”
Section: Bulletin Of the Iraq Natural History Museummentioning
confidence: 99%
“…During our field surveys, we encountered multiple other species of raptors inside the study area. We included their IUCN conservation status and their taxonomic order following Al-Sheikhly and Al-Azawi (2019b) DISCUSSION The Western marsh harrier has been a regular raptor in the Mesopotamian wetlands, having been recorded on a regular basis starting in the 1920s (Al-Sheikhly and Al-Azawi, 2019a). However, few research efforts have been conducted with regard to its migrating/wintering population.…”
Section: Bulletin Of the Iraq Natural History Museummentioning
confidence: 99%
“…The current study revealed to one voucher specimen of Eurasian Hobby which was collected from Baghdad province central of Iraq as shown in Plate (1). Eurasian Hobby was considered a rare winter visitor and passage migrant to the marshy lakes, cultivated fields on the Mesopotamian marshes (Cumming 1918;Ticehurst et al 1922;Fazaa et al, 2017;Al-Sheikhly and Al-Azawi, 2019).…”
Section: Species Status In Iraqmentioning
confidence: 99%
“…Worldwide, the genus Falco Linnaeus, 1758 contains 38 species (Myers et al, 2009); in Iraq, a total of ten species and subspecies including: Saker Falcon F. cherrug; Lanner Falcon F. biarmicus; Peregrine Falcon F. peregrinus; F. p. (brookei); Barbary Falcon F. p. (pelegrinoides); Eurasian Hobby F. subbuteo; Merlin F. columbarius; Red Footed Falcon F. vespertinus; Lesser Kestrel F. naumanni; Common Kestrel F. tinnunculus are recorded (Cumming,1918;Donald, 1919;Ticehurst et al, 1922;Meinertzhagen, 1914Moor and Boswell, 1956;Allouse,1960;Scott and Carp, 1982;Scott, 1993;Evans, 1994;Scott, 1995;Abed, 2007;Salim et al, 2009;Porter et al, 2010;Ararat et al, 2011;Al-Sheikhly, 2011;Al-Sheikhly, 2012a;Lahoney et al, 2013;Fazaa et al, 2017;Al-Sheikhly and Al-Azawi, 2019).…”
Section: Introductionmentioning
confidence: 99%